Biogenesis, delivery, and function of extracellular RNA. Issue 1 (28th August 2015) - Patton, James G.; Franklin, Jeffrey L.; Weaver, Alissa M.; Vickers, Kasey; Zhang, Bing; Coffey, Robert J.; Mark Ansel, K.; Blelloch, Robert; Goga, Andrei; Huang, Bo; L'Etoille, Noelle; Raffai, Robert L.; et al.
Abstract : The Extracellular RNA (exRNA) Communication Consortium was launched by the National Institutes of Health to focus on the extent to which RNA might function in a non‐cell‐autonomous manner. With the availability of increasingly sensitive tools, small amounts of RNA can be detected in serum, plasma, and other bodily fluids. The exact mechanism(s) by which RNA can be secreted from cells and the mechanisms for the delivery and uptake by recipient cells remain to be determined. This review will summarize current knowledge about the biogenesis and delivery of exRNA and outline projects seeking to understand the functional impact of exRNA.